Antiplasmodial activity-aided isolation and identification of quercetin-4 `-methyl ether in chromolaena odorata leaf fraction with high activity against chloroquine-resistant plasmodium falciparum - Ezenyi, I. C.; Salawu, O. A.; Kulkarni, R.; Emeje, Martins (Parasitology Research, 2014)
The present study was undertaken to evaluate the antiplasmodial activity of Chromolaena odorata leaf extract and gradient fractions through in vivo and in vitro tests, aimed at identifying its antiplasmodial constituents. Sub-fractions obtained from the most active gradient fraction were further tested for cytotoxicity against THP-1 cells, chloroquine-sensitive (HB3) and chloroquine-resistant (FCM29) Plasmodium falciparum. Our results showed the dichloromethane gradient fraction was most effective, significantly (P<0.05) suppressing infection by 99.46 % at 100 mg/kg body weight. Amongst its 13 sub-fractions (DF1-DF13), DF11 was highly active, with IC50 of 4.8 and 6.74 mu g/ml against P. falciparum HB3 and FCM29, respectively. Cytotoxicity of DF11 was estimated to be above 50 mu g/ml, and its separation by column chromatography yielded a flavonoid which was characterized as 3, 5, 7, 3' tetrahydroxy-4'-methoxyflavone from its spectroscopic data. It significantly suppressed infection (65.43-81.48 %) in mice at 2.5-5 mg/kg doses and compared favourably with the effects of chloroquine and artemisinin. It may therefore serve as a useful phytochemical and antiplasmodial activity marker of C. odorata leaves, which exhibit potential for development as medicine against malaria.
Keywords: malaria; Medicinal plant; Plasmodium falciparum; Toxicity